Crystal structure of 4-(dimethylamino)pyridin-1-ium-2,5-dichloro-3,6-dioxocyclohexa-1,4-diene-1,4-bis(olate) 4-dimethylaminopyridine (2:1) water undeca-solvate - Belay, Alebel Nibret; Venter, Johan Andries; Alexander, Orbett Teboho (European Journal of Chemistry, 2020)
The structure of the title compound, 4-(dimethylamino)pyridin-1-ium-2,5-dichloro-3,6-dioxocyclohexa-1,4-diene-1,4-bis(olate) 4-dimethylaminopyridine water undeca-solvate, C57H87Cl5N12O21, obtained from interaction between chloranilic acid (caH2), and dimethyl aminopyridine (DMAP) has been determined by single crystal X-ray diffraction. The title compound, (DMAPH)5(ca)2.5·(DMAP)·11H2O, crystallized in the triclinic crystal system with space group, P (no. 2), a = 13.3824(15) Å, b = 13.4515(17) Å, c = 19.048(2) Å, α = 86.014(4)°, β = 88.821(4)°, γ = 86.367(4)°, V = 3413.3(7) Å3, Z = 2, T = 100(2) K, μ(MoKα) = 0.294 mm-1, Dcalc = 1.414 g/cm3, 59413 reflections measured (3.76° ≤ 2Θ ≤ 56°), 16405 unique (Rint = 0.0517, Rsigma = 0.0589) which were used in all calculations. The final R1 was 0.0460 (I ≥ 2σ(I)) and wR2 was 0.1271 (all data). Using supramolecular chemistry principles, proton donors (chloranilic acid) and acceptor (DMAP) were combined to generate a multicomponent hydrogen-bonded system. Due to the presence of protonated bases (DMAPH+), the dominant interactions are the N+-H···O hydrogen bonds, whereas the negative charges of an acceptor from the chloranilate dianion (ca2-) are delocalized. Additionally, three sets of water clusters in the title compound were identified, namely a cyclic pentamer, a linear, and an acute-shaped trimer water cluster. It was further observed that strong hydrogen bond interactions occurred between the solvated aqua molecule(s) acting as a proton donor and the neutral DMAP acting as a proton acceptor. The crystal packing is further stabilized by O-H···Cl and C-H···Cl weak halogen interactions. The lattice metric strength is further held by observed π-π stacking interactions (centroid-centroid) with inter centroid distances between sets of the DMAPH rings of 3.624(3), 3.642(4), 3.739(3), 3.863(3) and 3.898(3) Å, respectively.